Surface morphological characteristics on unmodified cucurbita as a biosorbent potential for chloride and sulphate - Musa, Sabariah; Mohamad, Nur Huda (IJLRET, 2018)
Groundwater is a second thought for a safe water supply to fulfil the needs of living creatures on the earth surface. In Universiti Tun Hussein Onn Malaysia (UTHM), groundwater can be extracted from pumped well at Research Centre for Soft Soil Malaysia (RECESS) area, but the quality was not promising as drinking water supply. The purposes of this study were to characterize the surface morphology of unmodified Cucurbita as biosorbent for each part from peel, flesh and seed and determine the effectiveness of Cucurbita components by using biosorbent amount optimization. From the Scanning Electron Microscope (SEM) result, some porous surface texture was spotted and it was believed to assist in entrapping and adsorbing the contaminants exists in groundwater. The biosorption method involved Cucurbita components namely peel, flesh and seed as sorbent while the groundwater acted as solvent that contains chloride and sulphate ions as sorbate. Three parameters were assessed namely chloride, sulphate and pH on series of biosorbent amount which affects biosorption performance. The percentage of biosorbent for optimization that was analyzed in this study was 0.05%, 0.1%, 0.15% and 0.2%. The Ionize Chromatography (IC) result, peel was proven to be the most effective component in removing chloride and sulphate in groundwater by 16.8% and 12.8% respectively. Meanwhile the data obtained showed that increase in adsorbent amount helped in reducing the pH value of groundwater. Hence, as referred to the Drinking Water Standard published by Malaysia Ministry of Health, concluded that pH and sulphate exist within permissible limit which are 6.5-9.0 and 250 mg/L while chloride ceased to present within 250 mg/L boundary. As a conclusion, Cucurbita can be classified as a potential biosorbent for groundwater treatment but some improvements must be implemented to bring a significant impact for the benefit of mankind through a safe drinking water supply and cost effective treatment.